Motivation–Workload Paradox in Practice-Based Distance Learning: A Mixed-Methods Study at Indonesia Open University - Marisa Marisa; Murni Maulina; Muhammad Sulaiman; Susy Puspitasari; Dedy Aswan; Mohamad Adning; Johana Nurkhalifah (JTP - Jurnal Teknologi Pendidikan, 2026)
This study comprehensively explores the perceptions, experiences, and challenges faced by students in taking practical courses at the Faculty of Teacher Training and Education (FKIP), Universitas Terbuka (UT). Practical courses are frequently hampered and encounter obstacles in assignment completion. Employing a mixed-methods design with 307 participants from two study programs at Universitas Terbuka (UT), this research collected quantitative data (perceptions) and qualitative data (constraints). Descriptive quantitative results reveal a notable paradox: the majority of students reported high independent learning motivation (68% - 88%) and positive perceptions of lecturer guidance quality (82% - 97%). However, these findings contrast with the operational reality, where students overwhelmingly perceived the workload as high (above 90%). Thematic analysis of qualitative data identified three main constraints: time management due to work conflicts (33.7% in TPEN), technical constraints (internet network and learning platforms), and difficulties bridging theory and practice (47% in PBIN). It is concluded that the success of practical courses in distance learning is heavily influenced by external structural and logistical factors, such as learning environment stability and system design, which hinder the actualization of student motivation and self-regulation. Research implications recommend instructional design flexibility, workload adjustment, digital infrastructure strengthening, and the provision of multimodal materials (demonstration videos) to bridge the theory-practice gap. Theoretically, this study contributes by mapping how external structural limitations in distance education impede student self-regulation mechanisms despite high internal motivation.